PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN BANK KALSEL KANTOR CABANG UTAMA BANJARMASIN - Raissa Shiba Ramadhan; Nurul Wahyuni; Fitriyadi; Devi Rusvitawati (Smart Business Journal (SBJ), 2026)
Raissa Shiba Ramadhan. 2210412320002. (2026). The Influence of Occupational Drive and Institutional Climate on the Performance Outcomes of Staff Members at the Main Office of Bank Kalsel Located in Banjarmasin. Supervisor: Nurul Wahyuni. This research is constructed with the primary objective of examining the magnitude to which occupational motivation alongside the workplace setting contributes to and Exerts a determinative effect on the magnitude of personnel performance. The participants involved in this investigation are staff members stationed at the Central Branch Office of Bank Kalsel located in Banjarmasin. Respondent selection was executed by employing a saturated sampling technique, in which the totality of the population was encompassed as the research sample. Data collection procedures were undertaken via the distribution of systematically constructed questionnaires, whereas the analytical method implemented involved multiple linear regression modeling. The results demonstrate that, in a concurrent manner, both vocational impetus and the organizational milieu exert a statistically meaningful influence on the performance of employees. When assessed individually, work-related motivation exhibits a positive influence on employee performance. Likewise, the workplace environment also presents a favorable and positive contribution toward employee performance.